Determining Relative Degrees in the Delegation of Executive Authority - Wickesberg, Albert K. (Academy of Management Journal, 1958)
Focuses on the determination of relative degrees in the delegation of executive authority. Components that must be considered in any attempt to determine the relative amounts of delegation present in the performance of executive responsibilities; Quantifying degrees of delegation; Calculation of the degree of authority exercised in determining long range manufacturing planning.